Influence of ionisation track structure on 20 nm FDSOI transistor. (August 2021) - Zhang, Hao; Liu, Hongxia; Pan, Ziwen; Chen, Shupeng; Chen, Ruibo
Abstract: The response of a 20-nm fully depleted silicon on insulator (FDSOI) transistor under irradiation by heavy ions is analysed using GEometry ANd Tracking (Geant4) and Synopsys Sentaurus device simulations. Because of the huge energy fluctuations between thin silicon layers, the deposited energy calculated using surface linear energy transfer (LET) is imprecise under the incidence of heavy ions at very low energy (< 0.3 MeV/amu). The radial ionisation distribution range obtained by Geant4 decreases with an increase in ion mass at the same silicon depth (2 μm). Using radial ionisation distribution data in the electrical step of simulating a single event, the current peak value under irradiation by low-energy Xe ions is the highest value (229.6 μA), which reveals that low-kinetic-energy ions may cause damage larger than that caused by the incidence of high-kinetic-energy ions. Additionally, although the high-energy ions generate larger collected charges in the device, the larger deposited charges will minimise the resulting parasitic bipolar amplification gain. Highlights: The deposited energy calculated by surface Linear Energy Transfer (LET) is imprecise under very-low-energy ion irradiation. The radial ionization distribution range obtained by Geant4 codes decreases with the increase of ion mass. Low kinetic energy ions may cause damage larger than that caused by the incidence of high kinetic energy ions. The bigger deposited charges caused under high-energy ion irradiation will minimize the parasitic bipolar amplification gain.